As ciências agrárias e o cenário socioambiental amazônico: um estudo sobre a formação e atuação profissional a partir de cursos da Universidade Federal do Oeste do Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2021)
Faced with the socio-environmental challenges in the Amazon Biome, the role of agrarian professionals is essential. Thus, one enters the training field in Agricultural Sciences, which implies discussing the teaching of agricultural practices, for social transformations in favor of the preservation of biodiversity. This dissertation analyzes the training of agrarian professionals from the Animal Science and Agronomy courses at the Universidade Federal do Oeste do Pará (Ufopa). A descriptive research was carried out with a quali-quantitative approach, whose data were collected through bibliographic and documentary sources and application of a structured questionnaire based on the Likert Scale. This instrument was intended for course coordinators, Structuring Teaching Centers (NDEs), teachers, students and alumni. For the analysis of quantitative data, descriptive statistics were adopted; to qualitative, Content Analysis. In view of this, the results revealed: 66.66% of the Agronomy Coordinators and 57.14% of the Zootechnics partially agreed with the statement that professional profiles are consolidated to deal with the complexity of rural systems in the Amazon. Regarding knowledge in policies and management of environmental resources being attributes of the agrarian professional, 52.94% of Agronomy professors totally agreed, and 41.93% of Zootechnics partially agreed; of the graduates, 55.81% of those in Agronomy and 40.47% of those in Animal Science partially agreed with the statement that the subjects critically emphasized environmental issues, in favor of sustainable solutions. It is concluded that, for agrarian professionals to contribute to regional needs, the courses need to remedy weaknesses in training, such as reconciling education between productive development and environmental conservation.
Keywords: Educação - Amazônia; Ensino Superior; Ciências Agrárias; Pará (Estado); CNPQ::INTERDISCIPLINAR::DOCÊNCIA:ENSINO SUPERIOR:CIÊNCIAS AGRÁRIAS; POLÍTICAS PÚBLICAS, DIVERSIDADE E DESENVOLVIMENTO AMAZÔNICO.